Single-Dose versus Multiple-Dose Antibiotic Prophylaxis for Preventing Post Caesarean Section Infectious Morbidity in A Cyrene Teaching Hospital - Ramzi Mohamed; Hafsa Qiteesh; Huda Hussien (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Caesarean section is a common obstetric surgery associated with an increased risk of post-partum maternal infection, enhancing the requirement for perfect antibiotic prophylaxis with fewer side effects and lower cost, the aim of this study is to evaluate the efficacy of a single- dose antibiotic regimen versus a multiple-dose antibiotic regimen in preventing post caesarean infection. Methods. The current study was prospective comparative with parallel, balanced randomization. The study was carried out on 200 patients who were divided into two groups: Group A patients received a single dose of Ceftriaxone 1g intravenously 30-40 minutes prior to caesarean section, whereas group B patients received Ceftriaxone 1 g and Metronidazole 500 mg intravenously 30-40 minutes before caesarean section, followed by Cefixime 400 mg once daily for 5 days and Metronidazole 500 mg three times daily for 5 days. Results. There was no significant difference between both groups in terms of post-operative infection prevention, and there was no statistically significant difference between both groups in the incidence of wound infection 2% in group A and 3% in group B (p=1.000) whereas 5% of group A and 9% of group B developed post-operative febrile morbidity (p= 0.268). 2% of group A as well as 2% of group B developed endometritis (p=1.000). Conclusion. Single-dose antibiotic prophylaxis is equivalent to multiple-dose antibiotics prophylaxis in infection prevention after caesarean delivery.